Equilibrium Contracts for the Central Bank of a Monetary Union - Avinash Dixit; Henrik Jensen (Center for Economic Studies and ifo Institute (CESifo), 2000)
We consider the political economy of a monetary union wheremember governments attempt to influence the policy of the commoncentral bank. Modeling this as a common agency with incentivecontracts, we show that if incentives are all that matters for the bank,the equilibrium implements a weighted average of the countriesmost preferred policy. We then argue that making the bank inflationaverse and/or attentive towards the countries economicdevelopments is undesirable in this context.
Keywords: 330